1984
DOI: 10.1021/jf00123a040
|View full text |Cite
|
Sign up to set email alerts
|

Deethylsimazine: bacterial dechlorination, deamination, and complete degradation

Abstract: Enrichment cultures utilizing deethylsimazine (6-chloro-N-ethyl-l,3,5-triazine-2,4-diamine) as a sole nitrogen source were obtained from so5 that had had long exposure to s-triazine herbicides. A bacterium was isolated that utilized deethylsimazine quantitatively as a nitrogen source for growth, but only 1 mol of nitrogen was obtained/mol of deethylsimazine, whereas all six atoms in melamine were utilized.The bacterium, which was identified as a strain of Rhodococcus corallinus, converted deethylsimazine to 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 21 publications
5
56
0
1
Order By: Relevance
“…No accumulation of OEAT formed from CEAT was found in the incubation medium, presumably because of its deamination to OOET as shown previously with R. corallinus (8). We did observe the formation of OEAT from R. corallinus and from Rhodococcus sp.…”
Section: Identification Of Ceat Metabolitessupporting
confidence: 86%
See 2 more Smart Citations
“…No accumulation of OEAT formed from CEAT was found in the incubation medium, presumably because of its deamination to OOET as shown previously with R. corallinus (8). We did observe the formation of OEAT from R. corallinus and from Rhodococcus sp.…”
Section: Identification Of Ceat Metabolitessupporting
confidence: 86%
“…It is not clear if this observation is related to the fact that, unlike R. corallinus, Rhodococcus strain TE3 cannot utilize OOOT as a source of nitrogen for growth. The reported deaminase activity toward AAAT associated with s-triazine hydrolase (8,23) was not detectable in the Rhodococcus recombinants, which did not utilize AAAT as a source of nitrogen for growth.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…strain A (NRRL B-12227) was isolated as a melamine-utilizing bacterium from municipal sewage collected in Switzerland (Cook and Hütter 1981;Cook 1987) and was later reclassified as Acidovorax citrulli (Seffernick et al 2002;Schaad et al 2008). Another melamine-degrading isolate, Rhodococcus corallinus strain 11 (NRRL B-15444R), was obtained from soils that had been experimentally exposed to s-triazine herbicides for a long time (Cook and Hütter 1984;Cook 1987). R. corallinus was originally considered to be a junior synonym of Rhodococcus rubropertinctus in a DNA homology study (Mordarski et al 1980), and has since been reclassified as Gordonia rubripertincta (Stackebrandt et al 1988;Euzeby 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The amount of 14 CO 2 produced by mineralization of cyanuric acid would have increased with a longer incubation. It has been reported that a cyanuric acid-mineralizing population frequently occurs in natural environments 3,5,6) . The ring cleavage path- way of cyanuric acid has been also examined 4) .…”
Section: Mineralization Of Intermediary Metabolite Cyanuric Acidmentioning
confidence: 99%